Transgenerational epigenetics : evidence and debate - Tollefsbol, Trygve (Burlington : Elsevier Science, 2014)
Transgenerational Epigenetics provides a comprehensive analysis of the inheritance of epigenetic phenomena between generations. Recent research points to the existence of biological phenomena that are controlled not through gene mutations, but rather through reversible and heritable epigenetic processes. Epidemiological studies have suggested that environmental factors may be heritable. In fact, environmental factors often play a role in transgenerational epigenetics, which may have selective or adverse effects on the offspring. This epigenetic information can be transferred through a numb
Chapter 9 -- Histone-Mediated Transgenerational Epigenetics
Print version:: Tollefsbol, Trygve: Transgenerational Epigenetics
Includes bibliographical references at the end of each chapters and index.
Keywords: Epigenesis, Genetic; Epigenesis; Genetic regulation; SCIENCE -- Life Sciences -- Biochemistry; Epigenesis; Genetic regulation; Epigenesis, Genetic; Genetic Diseases, Inborn; Electronic books; Electronic books